2008
DOI: 10.2215/cjn.03420807
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Kidney Disease in Latin America

Abstract: Latin America is a conglomerate of adjacent countries that share a Latin extraction and language (Spanish or Portuguese) and exhibit extreme variations in socioeconomic status. End-stage renal disease prevalence and incidence rates have been growing steadily, probably as a result of the increase in life expectancy, aging of the population, a growing epidemic of type 2 diabetes, and a fast epidemiologic transition across the region. Chronic noncommunicable diseases impose an enormous cost, barely supported at p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
11

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 11 publications
0
40
0
11
Order By: Relevance
“…Although measures of CKD prevalence in Latin America are rare [34], reports from El Salvador and Nicaragua have estimated that 12.7 % of these populations are afflicted with CKD [35,36]. In addition, a recent survey examining CKD prevalence in Latin America reported the prevalence of proteinuria in Mexico and Chile to be 9.2 % and 14.2 %, respectively [37]. Notably, the definition of CKD used in these studies has varied including differences in thresholds defining proteinuria and eGFR, in equations used to calculate eGFR, and in the reliance on eGFR and proteinuria to define CKD.…”
Section: Discussionmentioning
confidence: 99%
“…Although measures of CKD prevalence in Latin America are rare [34], reports from El Salvador and Nicaragua have estimated that 12.7 % of these populations are afflicted with CKD [35,36]. In addition, a recent survey examining CKD prevalence in Latin America reported the prevalence of proteinuria in Mexico and Chile to be 9.2 % and 14.2 %, respectively [37]. Notably, the definition of CKD used in these studies has varied including differences in thresholds defining proteinuria and eGFR, in equations used to calculate eGFR, and in the reliance on eGFR and proteinuria to define CKD.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in CKD in Latin America has been attributed to demographic changes (aging population and rapid epidemiologic transition) as well as to an epidemic of obesity and type 2 diabetes [25]. Others have suggested that a significant contributor to the problem in Central Latin America is the high level of health care inequality, with the greatest burden of CKD mortality and morbidity being born by those who are uninsured in Mexico's health system [26].…”
Section: Relative Importance Of Ckd To Ylls and Dalys Across Nationsmentioning
confidence: 99%
“…Although data about chronic kidney disease are scarce, public health awareness is high, as evidenced by ongoing chronic kidney disease (CKD) detection programs. [11,12] The prevalence of ESRD is currently more than 2,000 per million population (p.m.p) in Japan. The estimated prevalence of a low GFR (< 60 mL/min/1.73 m 2 ) is 20% of the adult population.…”
Section: Introductionmentioning
confidence: 99%